Double Network Glycerol Gel: A Robust, Highly Sensitive, and Adaptive Temperature Sensor. Issue 11 (1st September 2021) - Feng, Zhanbin; Zhang, Ziteng; Chu, Bo; Zhang, Xing‐Hong
Abstract: Temperature sensors have great potential applications for the body temperature monitoring, it's a big challenge to prepare sensors with high sensitivity and maintaining adaptive properties for the long‐term applications. In this study, an organohydrogel for the temperature sensor is achieved via glycerol solvent replacement of water in the poly‐ N ‐acryloyl glycinamide (PNAGA)/carrageenans double network (DN) hydrogel. Owing to successful construction of strong multiple hydrogen bonding (H‐bonding) interactions among PNAGA chains and carrageenans, the PNAGA‐based glycerol gel (Gly‐gel) sensor exhibits excellent thermal stabilities, possesses high sensitivities (2% °C) resulted from the acceleration of mobility of ions at high temperature and shows high tensile strength of about 4 MPa without chemical crosslinkers (higher than most reported organohydrogel‐based temperature sensor) with self‐healable performance. In addition, the double network of Gly‐gel enables it excellent dual and triple shape memory performance with high fixing ratio ( R f, 88%), recovery ratio ( R r, 95%) under large deformations (above 80%) that are beneficial to the potential application in wearable devices. Different from previous temperature sensors, this work provides a facile approach to prepare overly sensitive temperature sensors with the combination of excellent thermal stability, high tensile strength and adaptive properties via the solvent replacement of hydrogel. Abstract : An organohydrogel‐based temperature sensor is achieved via glycerol solvent replacement of water in poly‐ N ‐acryloyl glycinamide/carrageenans DN hydrogel (Gly‐gel). The Gly‐gel sensor exhibits high sensitivities (2% °C −1 ) and shows high tensile strength of up to 4 MPa with self‐healable performance. The double network enables Gly‐gel excellent shape memory performance with high fixing ratio ( R f, 88%), recovery ratio ( R r, 95%).